Eating on the Eve of the Early Modern Period - Stephan F. Ebert (Clotho, 2024)
Between 1485 and 1487, the Patriarch of Aquileia sent the bishop of Caorle (Italy) to the Alps-Adriatic region to re-consecrate churches, chapels, and cemeteries that had been desecrated during the Turkish invasions. Among the travelers was the bishop’s private secretary, Paolo Santonino (ca. 1440–1507). He kept a diary of the journeys and recorded not only ecclesiastical matters but especially the daily meals served to the travel group. Since the travelers were of high status, the dishes were primarily late-medieval haute cuisine, as many recipes matched contemporary culinary literature. The preparation of these dishes presupposed culinary experts (e.g., chefs) and connections to trade networks, supplying the kitchen with exotic spices and ingredients. Books and other written forms of expert knowledge were also needed, and local products had to meet the high standards of sophisticated consumers. In the 1400s, the demands of these consumers were changing as foodstuffs from the Mediterranean were being introduced to the north of the Alps (e.g., asparagus, lettuce, saffron, spinach). This paper looks at the Alps-Adriatic region as a connecting area of this transformation process, focusing on particularly favorable areas such as the Illyrian Climate Region. It discusses the potential of Santonino’s Itinerarium by analyzing culinary and dietetic knowledge, local food production and consumption, and people involved in regional culinary practices.